Pengaruh E-Service Quality terhadap Repurchase Intention yang Dimediasi oleh Customer Satisfaction Pengguna E-Commerce Tokopedia di Kabupaten Bandung Barat - Zaelani, Arnie Shabrina; Adialita, Tania (Universitas Batanghari, 2024)
Since the advent ofÂ e-commerce, shopping patterns have shifted from traditional to more modern ones, where people can now shop online solely through smartphones. In Indonesia, there are numerous marketplace platforms such as Tokopedia, Shopee, Lazada, Bukalapak, and Blibli. In 2022, the number of e-commerce users in Indonesia reached 178,94 million, and it is projected to increase to 196,47 million by the end of 2023. Tokopedia is one of the leading e-commerce platforms in Indonesia. In 2020, Tokopedia ranked third in the category of online sales wensites as the e-commerce platform with the highest number of users in Indonesia. However, Tokopedia experienced a decline in index from 2021 to 2023, with a decrease of 5,4%. The aim of this research is to determine the effect of e-service quality on repurchase intention which is mediated by customer satisfaction of Tokopedia e-commerce users in West Bandung Regency. 90 respondents who used the Tokopedia e-commerce application participated in this research. A cross-sectional method or one-shot study was used to obtain data. Using SPSS 25 software, data analysis procedures for this research include the Sobel, test simple regression analysis, and multiple regression analysis. From the survey, it is found that the research results that e-service quality has a positive and significant effect on customer satisfaction. Then e-service quality also has a positive and significant influence on repurchase intention. Apart from that, customer satisfaction has a positive and significant effect on repurchase intention. Then, customer satisfaction succeeded in mediating the influence of e-service quality on repurchase intention.